Analisis Peran Media Sosial Instagram Terhadap Keputusan Pembelian Oleh Konsumen Explorer.IDN - Kristina, Kartika; Pusparani, Pusparani; Habibie, Fachrul Husain (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
This study aims to analyze the role of Instagram social media in influencing consumer purchasing decisions at Explorer.Idn as an online travel agent. This study employed a qualitative approach using a descriptive method. The research data were obtained through interviews with eight informants who had previously used Explorer.Idn travel services. Data were collected through video call interviews using an interview guide developed based on the research focus. The results indicate that Instagram social media plays an important role in influencing consumers’ purchasing decisions at Explorer.Idn. Consumers use Instagram to identify their travel needs, search for information about destinations, travel packages, prices, facilities, and services, and evaluate alternatives before making a purchase. Several Instagram features, such as follow, like, comments, mentions, and location, help consumers obtain information and increase their interest and trust in Explorer.Idn, while the hashtag feature has not been utilized optimally. Positive consumer reviews are also an important factor in building trust and encouraging purchasing decisions. After using Explorer.Idn’s services, most informants expressed satisfaction, willingness to make repeat purchases, and intention to recommend Explorer.Idn to others. Keywords: social media, Instagram, purchasing decision, online travel agent, Explorer.Idn